When Pets Attack Wildlife—Part 2: What to Do - Casey, Shirley; Goldthwait, Mackenzie (Wildlife Rehabilitation Bulletin, 2013)
Many wild animals are admitted to rehabilitation as a result of capture and injury by cats and dogs. Review of published literature, as well as discussions with veterinarians and wildlife rehabilitators, often focuses on use of antibiotics to address potential infections resulting from exposure to bacteria in the pet’s mouth. This paper offers some reminders to identify the full suite of possible conditions, to assess if the wild animal is able to survive and be released, and to consider then a range of possible treatment options—rather than automatically turning to antibiotics as a solution when antibiotics may not be appropriate nor the only option.